Analisis Putusan Hakim terhadap Pelaku Tindak Pidana yang Mengendarai Kendaraan Bermotor karena Kelalaiannya Mengakibatkan Orang Lain Meninggal Dunia di Wilayah Hukum Pengadilan Negeri Bajawa: Putusan Nomor 52/Pid.Sus/2020/PN.Bjw - Dania Anjali Khana Kale; Deddy R. CH. Manafe; Adrianus Djara Dima (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
This research aims to analyze the considerations of the Judge inimposing a prison sentence of 9 (nine) months on the Defendant who, due to their negligence in driving a motor vehicle, caused the death of another person, which has corresponded with the actions of the defendant and the facts presented in the trial. The type of research that the author uses is Normative Juridical research (library research), which is research that studies document analysis using various secondary data such as legislation, court decisions, legal theories, and can include the opinions of scholars. This research shows that (1) The judge in imposing a prison sentence of 9 (nine) months on the defendant did not consider the actions of the defendant sufficiently, so the application of the prison sentence of 9 (nine) months was not appropriate considering the actions of the defendant, which were that the defendant saw the victim from a distance of 50 (fifty) meters, but the defendant did not attempt to stop his vehicle, merely trying to change lanes, and the victim also moved to the same lane, making the accident unavoidable. (2) The judge's decision to impose a prison sentence of 9 (nine) months on the defendant was in accordance with the facts presented during the trial which included the Defendant's Testimony, the Indictment by the Public Prosecutor, and the Demands of the Public Prosecutor.